FOREIGN LANGUAGE AS AN INSTRUMENT OF DEVELOPING CRITICAL THINKING - Natalia Moskovskaya; Veronika Starichkova (Вестник Северо-Кавказского федерального университета)
The article deals with the problem of critical thinking as a core competence of the 21st century. The authors explain the content of the term "critical thinking" and give the system of its intellectual skills. They regard the possibilities of developing critical thinking skills while learning the language and come to the conclusion that studying foreign languages provides good opportunities for developing cognitive activities of the students including critical thinking skills. The article also provides the description of the methods of developing critical thinking skills in the process of language learning: stages of the educational process, techniques, exercises and required pedagogical conditions.